MEMBUAT DAISY DIGITAL TALKING BOOK (DTB) JENIS TOC ONLY DENGAN MENGGUNAKAN SOFTWARE SIGTUNA DAR 3 - Harjo Budi (Semantik, 2011)
Digital Talking Book (DTB) type is a type of DTB TOC Only the most simple and easily accessible to the blind, because this type of DTB containing only the title, subtitles, and page numbers only, while it is read out. DTB lainyya crate, this type of DTB could be accessed by reader like DTB DTB Player, TAB Player, and AmisKeyword : DTB,ToC Only, blind